การประยุกต์เทคนิคคิวเอฟดีเพื่อพัฒนาโครงสร้างระบบประกันคุณภาพ ในโรงพิมพ์ประเภทการผลิตหนังสือ : กรณีศึกษา - สายรุ้ง อินทร์เลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This research is the development of the quality assurance (QA) system structure in a book printing press. The main objectives of the QA system are (1) to establish customer satisfaction (2) to reduce mistakes in work and (3) to reduce production cost. The technique used in this research is Quality Function Deployment (QFD) with the Four-Phase model. The first phase "Product planning" that is the planning of QA system by translation the customer requirements and company requirements into technical responses, which are in the form of performance measures. The second phase "Product design", here is the designing of QA system structure and translate technical responses from the first phase into the characteristics of each QA system part. The third phase "Process planning", here is the planning and designing of processes and key process parameters within parts of QA system structure. These processes and parameters should be consistent with part characteristics from the second phase. The fourth phase "Process control planning", here is the planning of QA system control. This phase includes (1) QA system implementation planning (2) Process control planning for controlling parameters from the third phase to meet their targets and (3) Required document system planning. The QA system structure resulted from the research consists of five subsystems i.e. (1) Planning and Management system (2) Quality Control and Inspection system (3) Maintenance system (4) Customer service system and (5) Quality Audit system. The structure has totally 18 parts in these 5 subsystems with 2 parts are selected for implementation testing, "Quality Control and Inspection Planning" and "In-process Inspection". The assessment of this QA system structure is done by the company experts and concerned employee through the assessment form. The assessment form is separated into 2 sections, "the QA system parts that improve from the existing parts" and "the QA system parts that are the new development parts". The results show that in assessors opinions, the developed QA system structure is very useful and trend to have potential for establishing customer satisfaction. The assessment by performance measurement found that % Repaired cost of Film and Plate Department is reduced about 7.09% and Repaired Jobs Rate of this department is reduced about 2.66%.